2018
DOI: 10.1080/21691401.2018.1518911
|View full text |Cite
|
Sign up to set email alerts
|

A perfect stimuli-responsive magnetic nanocomposite for intracellular delivery of doxorubicin

Abstract: Iron oxide nanoparticles (IONs) have been extensively applied in cancer therapy and theranostics due to their admissible magnetic properties, excellent chemical stability and biocompatibility. Herein, a novel stimuli-responsive magnetic nanocomposite was synthesized for cancer therapy; thereby, the triblock copolymer of poly[(2-succinyloxyethylmethacrylate)-b-(N-isopropylacrylamide)-b-dimethylaminoethylmethacrylate) [poly(SEMA-b-NIPAM-b-DMAEMA)] was prepared by reversible addition of fragmentation chain transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Based on the in vitro drug release behavior dual responsiveness was observed leading to maintain the drug concentration at the target area. Further, the cytotoxicity results confirmed that the tailored formulation was more cytotoxic and biocompatible in contrast to native Dox [59] . Recently, an efficient ROS-sensitive sulfasalazine (SSZ) loaded magnetic nanosystem was developed for the treatment of rheumatoid arthritis (RA).…”
Section: Biomedical Application Of Hp-mnpsmentioning
confidence: 57%
“…Based on the in vitro drug release behavior dual responsiveness was observed leading to maintain the drug concentration at the target area. Further, the cytotoxicity results confirmed that the tailored formulation was more cytotoxic and biocompatible in contrast to native Dox [59] . Recently, an efficient ROS-sensitive sulfasalazine (SSZ) loaded magnetic nanosystem was developed for the treatment of rheumatoid arthritis (RA).…”
Section: Biomedical Application Of Hp-mnpsmentioning
confidence: 57%
“…A novel copolymeric system of poly[(2-succinyloxyethylmethacrylate)-b-(N-isopropylacrylamide)-b dimethyl aminoethylmetha- crylate) was fabricated by RAFT polymerization. Using succinyloxyethylmethacrylate, a triblock copolymeric system was coated on the surface of Fe 3 O 4 nanoparticles to aid in the delivery of anticancer drugs [ 187 ]. A dual pH- and magnetic field-responsive magnetite coated with Eudragit ® S100 was fabricated and loaded with amoxicillin.…”
Section: Stimuli-responsive Polymeric Nanocarriers For Drug and Gmentioning
confidence: 99%
“…AA), such functional groups can also be generated by the chemical modification of preformed non‐functional polymers. For example, Ghamkhari et al 58 . prepared dual stimuli‐RMPHs starting from poly(2‐hydroxyethylmethacrylate)‐ block ‐poly( N ‐isopropylacrylamide)‐ block ‐poly( N , N ‐dimethylaminoethylmethacrylate) triblock copolymers (PHEMA ‐b‐ PNIPAM ‐b‐ PDMAEMA), which do not form strong complexes with MNPs.…”
Section: Stimuli‐responsive Magnetic Polymer Hybridsmentioning
confidence: 99%